ETIKA AUDITOR MEMODERASI PENGARUH PENGALAMAN AUDITOR, KOMPETENSI DAN DUE PROFESSIONAL CARE PADA KUALITAS AUDIT - Ningrum, Krisna Dekna; Budiartha, Ketut Ketut Budiartha (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
The purpose of this study was to determine the effect auditor's experience, competence, due professional care on the quality of the audit by the auditor ethics as moderating variables. This research was conducted in the public accounting firm of Bali Province. The samples used as many as 40 people using sampling techniques saturated. Methods of data collection is done by using questionnaires and data analysis technique used is multiple linear regression analysis and moderated regression analysis. Based on the analysis found that the auditor's experience a positive effect on audit quality. Competence positive effect on audit quality. Due professional care positive effect on audit quality. Ethics auditor auditor strengthen the influence of experience on audit quality. Ethics auditor competence strengthening effect on audit quality. Ethics auditor strengthen the influence due professional care in audit quality.
Keywords: auditor' s experience, competence, due professional care, quality audit, and ethics of auditors